Utilization of Ice Breaking Techniques to Reignite Students' Engagement in Learning within Elementary Education - Rahma, Oktavianing Malikul; Abduh, Muhammad (Paedagogia: Jurnal Pendidikan, 2024)
It is common and often happens when the teaching and learning process occurs; students feel bored with learning. Teachers must be more creative in finding out the way to create more enjoyable learning. This study aims to understand the implementation of ice breaking so that every learner uses ice breaking to know the supporting factors and to overcome the inhibiting factors. This study uses a descriptive-qualitative approach. The subjects of this study were teachers as class teachers and class I.A. students. Data collection techniques in this study used interviews, observations, and documentation. The validity of the data in this study used source and technology triangulation. The interactive analysis model was used for data analysis in this study and was carried out in four stages: data collection, data reduction, data presentation, and drawing conclusions. The results showed that students were thrilled and interested in using ice-breaking in the teaching and learning process, which was carried out at the beginning, middle, and end of learning. Students' very high interest and interest affect student learning outcomes so that students can understand the learning material faster. For subsequent researchers, it is hoped that they can apply and find out about the types of ice breaking that can overcome student boredom and restore students' interest in learning.